Basic and Clinical Understanding of Microcirculation 2020
DOI: 10.5772/intechopen.90404
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Vascular Tone Regulation: Integration and Impact of Disease

Abstract: This chapter summarizes the current knowledge regarding the regulation of the tone of cerebral resistance arteries under conditions of normal health and with the development of chronic diseases (e.g., metabolic disease). The work integrates the myogenic (pressure-induced) regulation of vascular tone, the impact of elevated luminal flow or shear stresses, that of local tissue metabolic activity on vascular tone and the concept of neurovascular coupling (linking neuronal activity to the impacts on vascular diame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 191 publications
(216 reference statements)
0
4
0
Order By: Relevance
“…The circulation of the central nervous system is regulated in a complex manner and it is mainly controlled by local factors while the neural control, that is so critical in the systemic circulation, is relatively weak and even controversial in the cerebral circulation [ 7 , 8 , 9 ]. The local factors involve several mechanisms such as myogenic, flow or shear mediated and metabolic responses which were concisely reviewed recently [ 10 ] and only a brief summary is provided here. It is important to emphasize that the autoregulation of blood flow in the intracranial space is of great importance, and this is thought to be the result of a multi-factorial complex mechanism which involves myogenic response, shear stress, hyper- and hypocapnia and hypoxia as well [ 9 , 11 , 12 ].…”
Section: Factors Regulating Cerebrovascular Tonementioning
confidence: 99%
“…The circulation of the central nervous system is regulated in a complex manner and it is mainly controlled by local factors while the neural control, that is so critical in the systemic circulation, is relatively weak and even controversial in the cerebral circulation [ 7 , 8 , 9 ]. The local factors involve several mechanisms such as myogenic, flow or shear mediated and metabolic responses which were concisely reviewed recently [ 10 ] and only a brief summary is provided here. It is important to emphasize that the autoregulation of blood flow in the intracranial space is of great importance, and this is thought to be the result of a multi-factorial complex mechanism which involves myogenic response, shear stress, hyper- and hypocapnia and hypoxia as well [ 9 , 11 , 12 ].…”
Section: Factors Regulating Cerebrovascular Tonementioning
confidence: 99%
“…The regulation of vascular tone in cerebral vessels is a complex process that involves multiple factors and mechanisms [ 167 ], which include pressure-induced regulation, shear stress, local metabolism, and the control of vascular diameter by neuronal activity. As previously described, the presence of ROS, RNS, and antioxidants can result in vasodilatory and vasoconstrictive effects in cerebral blood vessels, with a complex interplay activity [ 168 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that TND could represent plateau waves or acute loss of local cerebral autoregulatory vascular tone 28 . Autoregulatory vascular tone is the autonomous ability of the brain to maintain and/or adjust perfusion pressure 37 . As a result of loss of autoregulatory tone, cerebral perfusion pressure (CPP) decreases, with subsequent lower CBF causing (relative) ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…28 Autoregulatory vascular tone is the autonomous ability of the brain to maintain and/or adjust perfusion pressure. 37 As a result of loss of autoregulatory tone, cerebral perfusion pressure (CPP) decreases, with subsequent lower CBF causing (relative) ischemia. The transient symptoms in this case could be related to changes in position (recumbent to supine), performance of the Valsalva maneuver or use of antihypertensive medication.…”
Section: Obstruction Of Blood Flowmentioning
confidence: 99%